Efficient and stable rice husk bioderived silica supported Cu2S-FeS for one pot esterification and transesterification of a malaysian palm fatty acid distillate - Albalushi, Mohammed Yousuf; Alsultan, G. Abdulkreem; Mijan, N. Asikin; Saiman, Mohd Izham; Tan, Yen Ping; Yap, Y. H. Taufiq (MDPI, 2022)
A novel heterogeneous catalyst composite (CuS-FeS/SiO2) derived from rice husk silica was engineered following pyrolysis, chemical precipitation, and chemical redox technique. The resulting catalyst was applied to the conversion of palm fatty acid distillate to biodiesel. The presence of CuS and FeS on the catalyst was verified using X-ray diffraction and Fourier transform infrared spectroscopy, nitrogen physisorption, scanning electron microscopy (FESEM) with energy dispersive X-ray (EDS) spectroscopy, and temperature-programmed desorption of NH3 (TPD-NH3), inductively coupled plasma-atomic emission spectrometry (ICP-AES), and TGA; a specific surface area of approximately 40 m2·g−1 was identified. The impact of independent variables, i.e., reaction temperature, reaction duration, methanol:oil ratio and catalyst concentration were evaluated with respect to the efficacy of the esterification reaction. The greatest efficiency of 98% with a high productivity rate of 2639.92 µmol·g−1·min−1 with k of 4.03 × 10−6 mole·S−1 was achieved with the following parameters: temperature, 70 °C; duration, 180 min; catalyst loading, 2 wt.%; and methanol to oil ratio, 15:1. The CuS-FeS/SiO2 catalyst showed relatively high stability indicated by its ability to be reused up to five times.